2020
DOI: 10.1038/s41598-020-77961-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum angiopoietin-like 3 levels are elevated in obese non diabetic men but are unaffected during an oral glucose tolerance test

Abstract: This study aimed to determine ANGPTL3 serum levels in healthy young lean and obese non-diabetic men during an oral glucose tolerance test (OGTT) and correlate them with anthropometric, biochemical and hormonal parameters. A case–control study was carried out and 30 young obese non-diabetic (23.90 ± 3.84 years and BMI 37.92 ± 4.85 kg/m2) and 28 age-matched healthy lean (24.56 ± 3.50 years and BMI of 22.10 ± 1.72 kg/m2) men were included in this study. The primary outcome measures were serum basal ANGPTL3 and AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…Our study showed that concentrations of ANGPTL3 were significantly lower in males than in females and that obesity had a strong effect on increasing ANGPTL3 levels in males. This finding is in accord with a significant positive correlation between ANGPTL3 and BMI in men and concurs with other observations demonstrating elevated levels of ANGPTL3 in severely obese young non-diabetic men and severely obese adolescents [14,20]. Interestingly, we found ANGPTL8 concentrations to be significantly lower in obese adolescents [20].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that concentrations of ANGPTL3 were significantly lower in males than in females and that obesity had a strong effect on increasing ANGPTL3 levels in males. This finding is in accord with a significant positive correlation between ANGPTL3 and BMI in men and concurs with other observations demonstrating elevated levels of ANGPTL3 in severely obese young non-diabetic men and severely obese adolescents [14,20]. Interestingly, we found ANGPTL8 concentrations to be significantly lower in obese adolescents [20].…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies revealed an association between ANGPTL3 and ANGPTL8 with lipid biomarkers in adults, young obese non-diabetic men, children, and adolescents with obesity and metabolic syndrome. However, very few of them stratified their data by gender [5,6,[14][15][16]. We selected circulating ANGPTL3 and ANGPTL8 to assess gender-specific relationships with obesity and biomarkers of atherogenic lipid profile in non-diabetic adults aged between 25 and 74 years.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies measuring plasma concentrations of ANGPTL3 in insulin-resistant states, such as obesity and type 2 diabetes, have yielded conflicting results. The majority of investigations have reported increased circulating ANGPTL3 in patients with obesity or T2D [21][22][23], whereas other studies have found that the plasma levels of ANGPTL3 are not higher in obese individuals than in controls [24,25]. The differences in the metabolic characteristics of the patients included in the various studies might have contributed to their discrepant outcomes, as suggested by our observation that, beyond obesity per se, the coexistence of metabolic abnormalities is associated with a substantial rise in circulating ANGTPL3.…”
Section: Discussionmentioning
confidence: 65%
“…It is worth mentioning here that previous works measuring ANGPTL3 levels in insulin resistance states such as obesity and T2D have produced conflicting results. Most studies report increased circulation of ANGPTL3 in obese or T2D patients [60,61], while other studies have found that ANGPTL3 levels are not higher in obese subjects than in controls [62].…”
Section: Discussionmentioning
confidence: 98%